2018
DOI: 10.1038/cr.2018.15
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen enhances stemness and promotes metastasis of ERα36+ breast cancer by upregulating ALDH1A1 in cancer cells

Abstract: The 66 kDa estrogen receptor alpha (ERα66) is the main molecular target for endocrine therapy such as tamoxifen treatment. However, many patients develop resistance with unclear mechanisms. In a large cohort study of breast cancer patients who underwent surgery followed by tamoxifen treatment, we demonstrate that ERα36, a variant of ERα66, correlates with poor prognosis. Mechanistically, tamoxifen directly binds and activates ERα36 to enhance the stemness and metastasis of breast cancer cells via transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
108
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 71 publications
7
108
0
2
Order By: Relevance
“…Interaction of these isoforms with the BMP signaling elements has not yet being investigated but could be involved in epithelial stem cell response to BMP2. Indeed, the importance of these different ERα isoforms in mammary epithelial SC features and in the context of breast cancer is only just starting to be identified [139,140]. These isoforms can be expressed in both ERα66-positive and -negative cells and display different subcellular localizations [141,142].…”
Section: Bmp and Er Crosstalkmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction of these isoforms with the BMP signaling elements has not yet being investigated but could be involved in epithelial stem cell response to BMP2. Indeed, the importance of these different ERα isoforms in mammary epithelial SC features and in the context of breast cancer is only just starting to be identified [139,140]. These isoforms can be expressed in both ERα66-positive and -negative cells and display different subcellular localizations [141,142].…”
Section: Bmp and Er Crosstalkmentioning
confidence: 99%
“…Interestingly, in the context of EDC research, ERα36 displays altered ligand preference and causes distinct effects compared to ERα66. For instance, the tamoxifen drug used as an estrogen antagonist in ERα66 breast cancers behaves as an estrogen agonist for ERα36 [140,144]. Collectively, these different examples illustrate how BMP signaling through its interaction with estrogen signaling is at the crossroad of a number of fundamental physiological processes.…”
Section: Bmp and Er Crosstalkmentioning
confidence: 99%
“…Exprese ERα36 může být využita pro rozdělení pa cientek do skupin, které budou, či nebudou mít prospěch z léčby TAM. TAM totiž může aktivovat ERα36, čímž podporuje buněčnou proliferaci a rozvoj metastáz [25]. U klinických vzorků rovněž odpovídá exprese ERα36 hladinám ALDH1A1 (aldehyde dehydrogenase 1A1).…”
Section: Genomický Mechanizmus Působení Erαunclassified
“…K potlačení těchto efektů TAM autoři navrhují terapii inhibitory ALDH1 nebo protilátkami specifi ckými proti ERα36. Nedávná studie rovněž ukazuje, že exprese ERα36 nemusí být pouze prognostickým bio markerem karcinomu prsu, ale ERα36 se v budoucnu může stát i potenciálním terapeutickým cílem [25].…”
Section: Genomický Mechanizmus Působení Erαunclassified
“…2 In a recent paper in Cell Research, Wang et al add to the evolving story the importance of ERα36 in breast cancer with a report that stimulation of ERα36 promotes metastasis via promotion of ALDH1A1-positive CSCs. 3,4 This group has previously reported that expression of ERα36 is related to resistance to tamoxifen, and that estrogen signaling via ERα36 regulates the maintenance of breast CSCs. 5 In the current study, they analyzed ERα36 expression in 1677 breast cancer samples, and convincingly showed that ERα36 expression was correlated with tumor size, grade, and lymph node involvement.…”
mentioning
confidence: 99%